Interactions between Anionic Polyacrylamide and Cationic Gemini/Conventional Surfactants. Issue 5 (27th March 2021) - Nishat, Afreen; Azum, Naved; Asiri, Abdullah M.; Sardar, Najam
Abstract: The interaction of anionic polymer polyacrylamide and cationic Gemini surfactants, namely: α, ω‐bis(hexadecyldimethylammonium)alkane dibromides, (16‐ s ‐16), s = 5, 6 and their conventional counterpart cetyltrimethylammonium bromide (CTAB) has been investigated by electrical conductivity, rheology, and scanning electron microscopy (SEM) techniques. Stronger interaction of Gemini surfactants in comparison to their conventional counterpart CTAB was observed from conductivity studies, while viscosity studies show that the interaction is quite significant with Gemini surfactants. The thermodynamic parameters for interactions show feasibility of interaction between the polymer and surfactant. SEM results support the viscosity data.